Sustainable Cities and Communities: Bibliometric Analysis of Research Trends and Scholarly Networks - Purwandari, Cornelia Ayu; Purwanto, Edi; Dewi , Cynthia Sari; Salsabil , Syifa Hanifa (International Journal of Business, Law, and Education, 2025)
This study presents a comprehensive bibliometric analysis of research trends, collaboration networks, and thematic developments within Sustainable Cities and Communities, aligning with Sustainable Development Goal 11 (SDG 11). Using the Scopus database, 107 relevant documents published between 1998 and 2024 were analyzed to identify patterns in scholarly output, publication types, influential sources, and international co-authorship. VOSviewer software was employed to generate visualizations, including co-authorship by country, keyword co-occurrence networks, temporal evolution, and density mapping of research focus areas. The findings reveal a significant increase in publication activity post-2015, following the global adoption of the 2030 Agenda. The United Kingdom, Netherlands, and Italy emerged as key contributors to international research collaborations. Thematic clusters primarily revolve around urban planning, sustainability frameworks, climate change, and SDG monitoring. Recent trends show a growing emphasis on climate adaptation and community engagement in urban sustainability. This study provides a structured overview of the intellectual landscape in sustainable urban development and highlights emerging research priorities. The insights can support scholars, policymakers, and practitioners in understanding the field's evolution and identify future directions for interdisciplinary and policy-relevant research.